In vitro Reconstitution and Analysis of the 6-Deoxyerythronolide B Synthase - Lowry, Brian (2013)
Notwithstanding an extensive literature on assembly line polyketide synthases such as the 6-deoxyerythronolide B synthase (DEBS), a complete naturally occurring synthase has never been reconstituted in vitro from purified protein components. Here, we describe the fully reconstituted DEBS and quantitatively characterize some of the properties of the assembled system that have never been explored previously. The maximum turnover rate of the complete hexamodular system is 1.1 min(−1), comparable to the turnover rate of a truncated trimodular derivative (2.5 min(−1)) but slower than a bimodular derivative (21 min(−1)). In the presence of similar concentrations of methylmalonyl- and ethylmalonyl-CoA substrates, DEBS synthesizes multiple regiospecifically modified analogs, one of which we have analyzed in detail. Our studies lay the foundation for biochemically interrogating and rationally engineering polyketide assembly lines in an unprecedented manner.